Estimation of Optimum Conditions for Cadmium Removal from Contaminated Soil using Electro-Kinetic Remediation - Hussein, Ahmed Alaa (Al-Nahrain Journal for Engineering Sciences, 2017)
The aim of this laboratory study is to estimate the best initial pH of purging solution for cadmium clean-up from an artificially contaminated soil using electro-kinetic cell. An efficiency enhancement scheme was employed involving pH control and injection wells as a part of the investigative program. Seven tests were performed at different pH controlled in the anode, cathode and injection wells start from 2 to 8. Sandy loam soil was contaminated with cadmium concentration equal to 2000 mg/kg and an initial moisture content equal to 30%. The duration of remediation was seven days with a potential gradient of 1.2 V/cm. The experimental results showed that the best removal efficiency was 62.8% at pH=3._x000D_ Keywords: , , , ,